Reforestration and management of mangrove swamp in Taklong Island, Guimaras - Baldevarona, Rodolfo B.
There were 101 families in the nine (9) fishing villages/clusters fronting Taklong Island, Guimaras. The families primarily subsisted in coastal fisheries including the utilization of the mangrove areas and beachcombing. The families belonged to way down below the poverty level. Freshly cut mangrove trees were seen and interview revealed that these wood were cut, bundled and marketed in Iloilo City as firewood and the stumps and other parts were converted into charcoal and sold. Mature seeds and very young seedlings gave significantly better survival compared to mature-leaved seedlings. Water dissolve oxygen, net primary productivity and soil total organic matter increased considerably from July 1988 to May1989. Other limnological parameters remained in their optimal levels except on inclement weathers where salinity and temperature were drastically affected.
Iloilo City : UPV-CFOS, 1989.